Peran kebijakan dividen terhadap enterprise value perusahaan sektor consumer staples di Indonesia - Melinda, Graceline; Wijaya, Feysya Sandrina; Widjaja, Audrey Cerelia; Linawati, Nanik (Nur Science Institute, 2025)
This study aims to analyze the effect of dividend policy on the enterprise value of consumer staples sector companies in Indonesia. This sector was chosen because of its important role in the economy and market stability. The main objective of this study is to identify the extent to which dividend policy can affect enterprise value in this sector. This study uses secondary data from Revinitif. Sample selection was carried out by purposive sampling. The control variables involved are return on assets, business size, and degree of financial leverage. The research method used is panel data regression with a fixed effect model approach. The results of the study show that the amount of dividends distributed does not have a significant effect on enterprise value. However, investors consider the level of return on assets, business size, and degree of financial leverage of the company more when making investment decisions.